THE FACTORS INFLUENCING MULTIDIMENSIONAL POVERTY OF HOUSEHOLDS: A CASE STUDY FROM BAC KAN PROVINCE - Le Dinh Hai; Nguyen Lan Huong (Journal of Forestry Science and Technology, 2022)
Multidimensional poverty is a novel approach that has been put into use in Vietnam in the period 2016-2020. This is a new basis for poverty assessment, prevailing the limitations of measuring by income. The study aims to determine key factors influencing multidimensional poverty and propose solutions to reduce multidimensional poverty for households in Luong Thuong commune, Na Ri district, Bac Kan province. By conducting a survey from 150 households in the study area and using Binary Logistic Regression model for data analysis, the study identifies five key factors significantly affecting multidimensional poverty of households in the study area, including: (1) land area of the household; (2) ability to access information by households; (3) participation in agriculture extension activities; (4) ethnicity of household head; and (5) number of dependant in the household. Based on that, four solutions were proposed to help households in study area escape from multidimensional poverty, including (i) increasing the land area for the poor household; (ii) improving access information for households; (iii) renovating agricultural extension; (iv) reducing the number of dependants in the household. These solutions can be used as valuable reference materials for developing policies of sustainable poverty reduction for households in the study area in particular and in whole country in general.